The iron silk road and North Korea: Is there any chance to move forward? - Bernhard Seliger (OrdnungsPolitisches Portal (OPO), 2021)
While Korea since several decades promotes an infrastructure project called "iron silk road", to link it with European markets, but also to integrate North Korea more into the world economy, these ideas largely ended nowhere. Instead, the Chinese proposal of the "One Belt, one Road" (short BRI) initiative, promoted since 2013 under the leadership of Xi Jinping, grew to a huge system of interrelated infrastructure projects, as well land-based as maritime. In these, the Korean Peninsula did originally did not feature. As an afterthought however, both were potentially included. South Korea's "New Northern Policy" under the Moon Jae-In administration to some extent is compatible with the BRI. North Korea did express a certain amount of interest in the initiative in a later stage, but the Covid-19 crisis for the time being led to complete isolation of North Korea and the stop of any larger international policy project. In the past, however, the policy of Special Economic Zones did follow the logic of market integration, which also the BRI follows. To understand the current reluctance of North Korea to participate in the BRI with more enthusiasm, once has to distinguish between the economic geography of North Korea, making such a participation desirable, and the political economy as well of the BRI as of North Korea. Since North Korea currently perceives economic opening, even to China, as a risk due to the inflow of new information and ideas not controlled by the state, for the time being North Korean participation is very doubtful, even after the resolution of the Covid-19 crisis
Keywords: 330; Iron Silk Road; North Korea; South Korea; economic geography; political economy; BRI